PELATIHAN PERTOLONGAN PERTAMA PADA KECELAKAAN UNTUK UNTUK ANAK USIA DINI - Imrotul Ummah; Rachma Hasibuan (CV. ADIBA AISHA AMIRA, 2025)
In early childhood, the accident rate is quite high. Efforts that can be made to overcome this are by providing health education knowledge in the form of training to parents about First Aid for Child Accidents. The aim of this activity is to provide knowledge to participants so they can provide first aid for child accidents. This program provides training with lectures and discussions as well as direct practice. The participants were 6 Talia Insan Mulia family planning teachers and 50 members of the Talia Insan Mulia Family Planning Association committee. Knowledge scores were measured before and after training. The average pre test score is 65.17 while the average post test score is 92.34. From this value, there is an increase in the average value of 27.17. In conclusion, there was an increase in first aid knowledge and skills in accidents after training.